ANALYSIS OF THE UNDERSTANDING OF MICRO BUSINESS ACTORS ON THE USE OF BPKB ARRUM LOANS PT. PEGADAIAN SYARIAH - Marina Zulfa; Ficha Melina; Zulkifli; Hamzah (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
Sharia pawnshops are a type of business entity where individuals can obtain funds to help meet their financial needs. Pegadaian Syariah provides a variety of products and services that can help people overcome their financial problems. One of its superior products is Ar Rum, a financing program to empower MSMEs that use BPKB as collateral. The BPKB guarantee will remain under the control of Pegadaian, so that customers can still use their vehicles. This study aims to investigate the impact of Understanding on Arrum BPKB loan applications at PT. Sharia Pawnshop. The results showed that there was a significant relationship between the level of understanding in the decision-making process. In other words, the greater a person's understanding of business and financial aspects, the more likely they are to be interested in applying for a loan to a Sharia Pawnshop.